Strategi Komunikasi Kebijakan Pembayaran Iuran Operasional TPS3R di Desa Pejeng (Social Interaction Patterns in Shops - I Putu Agus Yamuna Sudiarta; Nyoman Diah Utari Dewi (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: The purpose of this study was to determine the communication strategy for the payment of TPS3R operational fees in Pejeng Village. Methodology: This study uses qualitative research methods with a descriptive approach. The object of this research is the implementation of the TPS3R policy in the village which is devoted to the communication strategy for paying TPS3R operational fees. The collection of data and information was carried out using observation and interview techniques. Data analysis techniques were carried out according to Miles and Huberman's analysis stages. Results: The results of this study are that the communication strategy for TPS3R contribution payment policies in Pejeng Village is carried out with five steps of communication strategy which includes the stage of finding out the characteristics of the community (research), then planning, then executing, namely conducting socialization and payment using QRIS, then do an evaluation (measure), and finally do a report. Limitations: The limitation of this research is that it only focuses on one village, namely Pejeng Village. Contributions: This research contributes specifically to the operation of TPS3R in Pejeng Village and provides information related to the application of appropriate communication strategies to facilitate the withdrawal of contributions related to TPS3R operations, especially in Gianyar Regency, and the results of this study can also be used as a reference for further research, especially in the disciplines of government and communication science.